2020
DOI: 10.1177/0954407020973816
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental research on flow and aerodynamic noise characteristics of coach

Abstract: The researches on flow and aerodynamic noise characteristics of coaches are urgently needed to improve with the rapid development of new energy coaches. In this paper, tests in model wind tunnel and numerical calculations were carried out to study the phenomenon of flow and aero-noise on 1:25 scale model coach. Based on large eddy simulation (LES) and detached eddy simulation (DES), reliable numerical calculation method of flow and aero-noise on coach was established and verified. It is found that the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As the number of meshes increases, the variation in the solutions obtained for the aerodynamic characteristics decreases. Further, the enormous number of meshes increases both the likelihood of obtaining a solution that is grid-independence 28 and the accuracy of the numerical solution of the simulated k ω SST turbulence.…”
Section: Numerical Calculation Methodsmentioning
confidence: 99%
“…As the number of meshes increases, the variation in the solutions obtained for the aerodynamic characteristics decreases. Further, the enormous number of meshes increases both the likelihood of obtaining a solution that is grid-independence 28 and the accuracy of the numerical solution of the simulated k ω SST turbulence.…”
Section: Numerical Calculation Methodsmentioning
confidence: 99%
“…9 The wake flow of rearview mirror for coach is analyzed by POD. 10 It is found that the energy of first mode is 6.1%, and only the first nine modes have an energy for more than 3.0%. By the reconstruction of first four modes, it can be seen that the complicated transverse vortex shedding couples with A pillar vortex and reaches the body surface.…”
Section: Introductionmentioning
confidence: 91%